Novel coronavirus mutations: Vaccine development and challenges. (December 2022) - Luo, Wan-Rong; Wu, Xiao-Min; Wang, Wei; Yu, Jun-Ling; Chen, Qing-Qing; Zhou, Xue; Huang, Xin'er; Pan, Hai-Feng; Liu, Zhi-Rong; Gao, Yong; He, Jun
Abstract: The ongoing global pandemic of novel coronavirus pneumonia (COVID-19) caused by the SARS-CoV-2 has a significant impact on global health and economy system. In this context, there have been some landmark advances in vaccine development. Over 100 new coronavirus vaccine candidates have been approved for clinical trials, with ten WHO-approved vaccines including four inactivated virus vaccines, two mRNA vaccines, three recombinant viral vectored vaccines and one protein subunit vaccine on the "Emergency Use Listing". Although the SARS-CoV-2 has an internal proofreading mechanism, there have been a number of mutations emerged in the pandemic affecting its transmissibility, pathogenicity and immunogenicity. Of these, mutations in the spike (S) protein and the resultant mutant variants have posed new challenges for vaccine development and application. In this review article, we present an overview of vaccine development, the prevalence of new coronavirus variants and their impact on protective efficacy of existing vaccines and possible immunization strategies coping with the viral mutation and diversity.